The The Use of Appraising Items in Doyle’s Novel Titled A Study in Scarlet - Rahimi, Ranti Harvi; Fitriati, Sri Wuli; Sutopo, Djoko (English Education Journal, 2019)
This research investigated the interpersonal meaning in A Study in Scarlet, how the appraising items used by the main characters and also its pedagogical implication to English education by using the framework by Halliday (2004) and Kress van Leeuwen (2006). The objectives of this research were to explain the use of the attitude, consisting of affect, judgment, and appreciation. This research was a discourse analysis which belongs to qualitative research. The source was nine chapters from the novel which is divided into two parts. The object was the utterances from the main characters. The units of the research were the clauses consisted in the chapters. The finding showed that the use of the attitude was dominated by Dr. Watson as the main character and also the narrator. In affect, he used mostly happiness, negative capacity, normality in judgment and positive reaction in appreciation. It can be concluded that the writer portrayed Sherlock Holmes through Dr. Watson’s utterances and monologues in order to show Holmes characters, how he reacted to series of events in the novel by using certain appraising items. By applying appraising items in teaching-learning, this research hopefully could help students to enhance their interpersonal skills in communication inside or outside the classroom to reach the purpose of having varied and natural conversation also a mutual understanding.